PENGARUH MODEL NHT (NUMBERED HEADS TOGETHER) BERBANTUAN E-MAGAZINE DINO TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN DEMANGAN 2 - Fatimah Azzahra; Aditya Dyah Puspitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is a quantitative study that aims to determine the effect of using the NHT (Numbered Heads Together) model assisted by DINO E-Magazine on social studies learning outcomes of fourth grade students of SDN Demangan 2. The research design used was one group pre-test post-test. The sample in this study consisted of 24 fourth grade students of SDN Demangan 2, namely 11 male students and 13 female students. The sampling technique used was saturated sampling. Data collection techniques in this study include interviews, questionnaires, observation and documentation. The results showed that there was a significant effect of the application of the NHT (Numbered Heads Together) model assisted by DINO E-Magazine on the social studies learning outcomes of fourth grade students of SDN Demangan 2. This is evidenced by the paired sample t-test with t count of 3.375 which is greater than t table which is 2.068, so H0 is rejected and Ha is accepted. The significance value obtained is 0.003 <0.05. The average pre-test score of 66.25 increased to 80 in the post-test score, which showed a significant difference in average scores between before and after treatment.